On the Borderline between Consensus and Reception: The Spirituality of Openness as a Necessary Criterion for Ecumenical Reception - Okpaleke, Ikenna Paschal (Journal of ecumenical studies, 2018)
Ecumenical dialogues often appear to be stalled by the inability of churches to make necessary transition from consensus to reception. This essay delves into the problematics of reception, addresses the key obstacles to ecumenical reception, and identifies openness as a necessary criterion for making the transition to reception. It represents an attempt to deepen the narrow idea of openness toward the ecumenical other by reconceptualizing openness as a form of spirituality, one that is essential for ecumenical fruitfulness.